Size Spectra of the edaphic fauna of Argiudol typical soils of the rolling Pampa region, Argentina [DATASET] - Velazco, Víctor Nicolás (2023)
Fil: Velazco, Víctor Nicolás. Universidad Nacional de Luján. Departamento de Ciencias Básicas; Argentina.